SIGGRAPH Asia 2014 Technical Briefs 2014
DOI: 10.1145/2669024.2669039
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of 2D flow fields using stream functions

Abstract: Recently, visual simulation of fluids has become an important element in many applications, such as movies and computer games. These fluid animations are usually created by physically-based fluid simulation. However, the simulation often requires very expensive computational cost for creating realistic fluid animations. Therefore, when the user tries to create various fluid animations, he or she must execute fluid simulation repeatedly, which requires a prohibitive computational time. To address this problem, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Flow deformation By using scalar stream functions, we have previously shown that 2D flow fields can be deformed while guaranteeing the incompressibility [18]. In this paper, we show that 3D flow fields can be deformed in an incompressible way as well, by using vector potentials.…”
Section: Model Reductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Flow deformation By using scalar stream functions, we have previously shown that 2D flow fields can be deformed while guaranteeing the incompressibility [18]. In this paper, we show that 3D flow fields can be deformed in an incompressible way as well, by using vector potentials.…”
Section: Model Reductionmentioning
confidence: 73%
“…For the sake of visual clarity, we used a 2D flow field as demonstration. The 2D analog of the 3D vector potential is a scalar function called stream function, computed from the 2D velocity field using our previous work [18].…”
Section: The Importance Of Divergence-free Aware Deformationmentioning
confidence: 99%